Agnes Aubert's mystical cat shelter - Fawcett, Heather (Heather M.) (Del Rey, an imprint of Random House, 2026)
"Agnes Aubert leads a meticulously organized life, and she likes it that way. As the proudly type-A manager of a cat rescue charity, she has devoted her life to finding forever homes for stray cats. Now it's the shelter that needs a new home. And the only landlord who will rent a space to a cat rescue is a mysterious man called Havelock--who also happens to be the world's most infamous magician, running an illegal magic shop out of his basement. Havelock is cantankerous and eccentric, but not not handsome, and no, Agnes absolutely doesnot feel anything but disdain for him. After all, rumors swirl about his shadowy past--including whispers that his dark magic once almost brought about the apocalypse. Then one day a glamorous magician comes looking for Havelock, putting the magic shop--and the cat shelter--in jeopardy. To save the shelter, Agnes will have to team up with the magician who nearly ended the world . . . and may now be trying to steal her heart. Havelock is everything Agnes thinks she doesn't need in her life: chaos, mischief, and a little too much adventure. But as she gets to know him, she discovers that he's more than the dark magician of legend, and that she may be ready for a little intrigue--and romance--in her life. After all, second chances aren't just for rescue cats. . . ."--